ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA PT BANK MUAMALAT INDONESIA TBK PERIODE 2016 – 2020 - Muhlis Muhlis; Devi Eka Putri (Economicus : Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine the health level of PT Bank Muamalat Indonesia Tbk using the Risk-based Bank Rating method in accordance with POJK Number 8/POJK.03/2014 concerning the Assessment of the Soundness Level of Islamic Commercial Banks and Sharia Business Units. This assessment covers 4 aspects, namely: Risk Profile, Good Corporate Governance, Earnings, and Capital or commonly called RGEC. This research uses a quantitative approach method. The data studied are quantitative data sourced from the annual financial statements and GCG reports of PT Bank Muamalat Indonesia Tbk for the period 2016 – 2020. The data collection technique in this study uses the documentation method. The data analysis technique used is descriptive analysis technique with the Risk-based Bank Rating or RGEC method consisting of Risk Profile (NPF and FDR), Good Corporate Governance (bank self-assessment), Earnings (ROA, ROE, and BOPO), and Capital (CAR). The results of this study indicate that during 2016 - 2020 the health level of PT Bank Muamalat Indonesia Tbk is in the position of Composite Rank 4 (PK 4) which is categorized as "unhealthy".